Using Assessments of Dental Students' Entrepreneurial Self‐Efficacy to Aid Practice Management Education. Issue 6 (1st June 2017) - Mollica, Anthony G.; Cain, Kevin; Callan, Richard S.
Abstract : In the past, the typical practice management curriculum in U.S. dental schools was found to place a heavy emphasis on customer service, whereas areas typically stressed in business entrepreneurship and management courses (e.g., long‐range planning, competing strategies, and supplier relationship) received less attention. However, future dentists will likely have many points in their careers at which they must decide whether to begin a new business or to associate with a practice, and entrepreneurial and management training can help them make and implement those decisions. The aim of this exploratory study was to investigate the impact of one dental school's practice management education on students' entrepreneurial self‐efficacy (ESE), a construct examined for the first time in dental education. ESE is an individual's belief that he or she is personally capable of planning for, operating, and managing a successful business. In December 2014, all students in all four classes were asked to complete a survey measuring their ESE. The response rates for each class were D1 94%, D2 91%, D3 87%, and D4 79%. The results showed that the mean scores of the fourth‐year class were higher on all five examined dimensions than those of the other three classes. The same was true for the mean for each class with the exception of the competency regarding an individual's perception of his or her abilities to deploy and manage human resources, in which the first‐year class had a higher score than the fourth‐year class (149.07>146.06). The fourth‐year class had statistically significant higher scores than the third‐year class, consistent with the implementation of practice management courses in the curriculum.